Therapeutic delivery of calcitonin to inhibit external inflammatory root resorption. I. Diffusion kinetics of calcitonin through the dental root - Wiebkin, O W; Cardaci, S C; Heithersay, G S; Pierce, A M (Endodontics & dental traumatology, 1996)
Insertion of calcitonin into root canals of monkey teeth has been shown to inhibit external inflammatory root resorption and suppress inflammation. Regulation of this therapeutic event depends upon the rate of arrival (diffusion) of the hormone at sites of resorptive activity. In the present study, the diffusion characteristics of calcitonin through the dental root in an extracted human-tooth model are described, and the role of cementum in the diffusion process is also addressed. Root-canals were endodontically prepared to form a reservoir for [125I]-calcitonin, and macerated to remove organic material from dentinal tubules. In teeth with intact cementum, an initial period of delay (4-5 h) prior to the detection of calcitonin at the external tooth-root surface was followed by a rapid release of the calcitonin during the first 10.5 h (rate peaks at 6 h). Slower, sustained releases of calcitonin through intact cementum were measured for the following 9 days. Removal of cementum, to expose "smear-free" dentine, resulted in an earlier efflux of calcitonin (2 h) at external tooth surfaces and increased amounts of calcitonin release over 9 days. Biphasic delivery of calcitonin by such internal diffusion mechanisms suggests that loss of cementum will enhance therapeutic availability, while prolonged delivery to intact external dental-root surfaces following early intra-canal placement may also be useful for the therapeutic prevention of external inflammatory root resorption.